Niveles de Tetraiodotironina (T4) en vaquillonas del norte de la Pcia. de La Pampa (Veterinary Science, 2017)
The objective of the work was to know the reference values of thyroxin (T4) hormone under grazing condition of beef cattle in the northwest area of La Pampa. Hundred eighteen blood samples from bovine allocated in six beef farms at the Department of Realico, Chapaleufú,Maracó and Quemú-Quemú were evaluated as consequence of different feeding type.The values founded in bloodT4 concentration varied in relation to the amount of iodine concentration in the feedstuff, being the lowest values at the Rancul department.
Keywords: T4; Beaf Cattle